(untitled) (Community Based Medical Journal, 2026)
Postoperative feeding protocols following spinal anesthesia vary widely, with traditional practices often delaying oral intake due to concerns about gastrointestinal complications. However, emerging evidence suggests that early feeding may accelerate recovery without increasing adverse effects. In resource-limited settings in Bangladesh, optimizing postoperative care is crucial for reducing hospital stays and enhancing patient outcomes. A prospective, cross-sectional study was conducted at Community Based Medical College, Bangladesh (CBMC,B) Hospital in Mymensingh, Bangladesh, from January to June of 2025, to assess the safety and efficacy of early oral feeding after spinal anesthesia by evaluating its impact on gastrointestinal tolerance, return of bowel function, and overall recovery time. Using purposive sampling, 93 adult patients undergoing spinal anesthesia were enrolled. Early oral feeding (within 2 hours postoperatively) was initiated, and outcomes— including nausea, vomiting, time to first flatus, and patient satisfaction—were recorded. Data were analyzed using SPSS version 23.0, with descriptive statistics, chi-square tests, and independent t-tests applied as appropriate. Early oral feeding was well-tolerated in 78.5% of patients (n=93), with only 12.9% experiencing mild nausea (p>0.05). Time to first flatus was significantly shorter (8.2±2.1 hours vs. 12.6±3.4 hours; p<0.001) compared to historical data. Patient satisfaction scores were higher in early-fed patients (85.2% vs. 62.1%; p<0.01), with no cases of aspiration or severe vomiting. Hospital stay was reduced by 8.4 hours (p<0.05). Early oral feeding post-spinal anesthesia is safe and enhances recovery, demonstrating faster gastrointestinal return (8.2 hours), higher patient satisfaction (85.2%), and reduced hospitalization without increasing complications. Our findings support implementing early feeding protocols in clinical practice to optimize postoperative outcomes. CBMJ 2026 January: vol. 15 no. 01 P:78-83